Analisis Yuridis Aksi Korporasi Badan Usaha Milik Negara (BUMN): Kasus Ex-Dirut Pertamina - Rachmat A Abdoellah (Jurnal Hukum Lex Generalis, 2025)
Behind her success, Karen Agustiwan was also involved in two highly controversial legal cases that caught public attention. This study aims to examine both cases using legal and philosophical foundations in the context of corruption in the state-owned enterprise sector and to provide recommendations for improvements in the framework of Good Corporate Governance to support the Business Judgment Rule, especially for business transactions abroad. Both cases indicate the abuse of authority and disregard for investment procedures in state- owned companies. To prevent similar cases from recurring, every investment project must undergo documented due diligence, feasibility studies, and risk assessments.